The use of English articles by a group of EFL learners. - Hasbún Hasbún, Leyla (2012)
This study analyzes the written production of a group of English-as-a-foreign-language students in order to determine the errors concerning the use of articles that students make. Results show that the most common type of mistake in all levels tends to be the overuse of articles. This happened in six out of eight groups. This type of mistake represents from 40 to 58.82% of the article errors. The article claims that this is partly due to first language interference. There is also evidence that indicates that overuse tends to decrease but not in a significant way.